Improving Text Descriptive Writing Skills In Middle-School Students: Investigating Image Media - Suparman, Rostina Andi; Amra Ariyani; Nurul Asma (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
This research aims to improve students' skills in writing descriptive text through the use of image media for class VII students at SMPN Satap Lelumpang. The low pre-test results of students are caused by teachers still using conventional methods of teaching writing. So the researchers decided to use a new method that had never been used before, namely using image media. The research carried out was classroom action research in two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. The research was carried out at SMPN Satap Lelumpang, with the research subjects being class VII students. Data collection techniques include written tests and observation sheets. The results of research using image media show a significant increase. This can be seen from the students' learning results: in Cycle I, the average score was 4.87 in the poor category, increasing to 8.32 in the good category in Cycle II. The completeness of learning outcomes increased from 48.1% in Cycle I to 92% in Cycle II. This shows that students' skills in writing descriptive text increase through the use of image media.